A Nanostructured Molybdenum Disulfide Film for Promoting Neural Stem Cell Neuronal Differentiation: toward a Nerve Tissue‐Engineered 3D Scaffold. Issue 5 (25th April 2017) - Wang, Shu; Qiu, Jichuan; Guo, Weibo; Yu, Xin; Nie, Jinhui; Zhang, Jian; Zhang, Xiaodi; Liu, Zhirong; Mou, Xiaoning; Li, Linlin; Liu, Hong
Abstract : Physical cues from nanostructured biomaterials have been shown to possess regulating effects on stem cell fate. In this study, nanostructured molybdenum disulfide (MoS2 ) thin films (MTFs) are prepared by assembling MoS2 nanosheets on a flat substrate. These films are used as a new biocompatible platform for promoting neural stem cell (NSC) differentiation. The results show that the nanostructured MTFs exhibit significantly positive effects on NSC attachment and proliferation without measurable toxicity. More importantly, immunostaining and real‐time polymerase chain reaction assessments show that the nanostructured MTFs induce NSC differentiation into neural cells at higher efficiency. It is found that the MTFs have a good electrical conductivity and offer larger surface areas for NSC attachment and spreading compared with conventional tissue culture plates. Furthermore, multilayered cylindrical 3D living scaffolds are constructed by rolling up NSC‐cultured MoS2 ‐polyvinylidene fluoride (PVDF) nanofiber films that are prepared by chemically assembling MoS2 nanostructures on electrospun PVDF flexible films. These living nerve scaffolds have a great potential for applications in nerve regeneration as cylindrical 3D living scaffolds. Abstract : A conductive and nanostructured molybdenum disulfide thin film (MTF) is prepared and used as a biocompatible platform for promoting neural stem cell (NSC) differentiation. The results show that the nanostructured MTF exhibits positive effects on NSC attachment, spreading, and communication, which makes MTFs potential candidates in nerve regeneration.